Tinjauan Kriminologi dan Penegakan Hukum Tindak Pidana Pencabulan Anak di Kota Pati (Studi Kasus di Unit PPA Polresta Pati) - Megayuniar, Fara; Wibowo, Ari (Prosiding Seminar Hukum Aktual Fakultas Hukum Universitas Islam Indonesia, 2025)
Abstract Child molestation cases in Pati City were recorded at a total of seven incidents between 2021 and 2023. Most of the perpetrators admitted that the victim was their underage girlfriend. This phenomenon indicates a shift in societal values that tend to tolerate romantic relationship with minors, thereby increasing the risk of sexual violence against children. The focus in this research focus on the factors that contribute to the occurrence of criminal act of child molestation and the struggle of the law enforcement. The research method used is a sociological approach with the type of empiric research. The results of this research show, first, that the factors causing the criminal act of child molestation in Pati City include individual, environmental, and family factors. Second, the enforcement of the law against child molestation is carried out by Polresta Pati through preemptive, preventive, and repressive measures. The struggle encountered by Polresta Pati in law enforcement include uncommunicative victims, the reported suspect who denies the accusation, delayed reporting resulting in the absence of medical evidence, and the lack of witnesses and evidence due to the incident occurring in a private setting.